Hot Balloon Versus Cryoballoon Ablation for Atrial Fibrillation: Lesion Characteristics and Middle-Term Outcomes. (May 2018) - Nagashima, Koichi; Okumura, Yasuo; Watanabe, Ichiro; Nakahara, Shiro; Hori, Yuichi; Iso, Kazuki; Watanabe, Ryuta; Arai, Masaru; Wakamatsu, Yuji; Kurokawa, Sayaka; Mano, Hiroaki; Nakai, Toshiko; et al.
Abstract : Background: Hot balloon ablation (HBA) and cryoballoon ablation (CBA) were developed to simplify ablation for atrial fibrillation. Because the lesion characteristics and efficacy of these balloon modalities have not been clarified, we compared lesion characteristics and outcomes of HBA and CBA. Methods: Of 165 consecutive patients who underwent initial catheter ablation for atrial fibrillation, 74 propensity scorematched (37 HBA and 37 CBA) patients were included in our study. Results: Patients' clinical characteristics, including age, sex, body mass index, atrial fibrillation subtype, CHA2 DS2 -VASc score, and left atrial dimension, were similar between the 2 groups. Touch-up radiofrequency ablation was required for residual/dormant pulmonary vein conduction in 52% of the patients with HBA versus 24% of the patients with CBA ( P =0.02) and often in the anterior aspect of the left superior pulmonary vein after HBA (41%) versus the inferior aspect of the inferior pulmonary veins after CBA (22%). HBA lesions were smaller than CBA lesions (23.8±7.9 versus 33.5±14.5 cm 2 ; P =0.0007). Similar results were observed when lesions in each pulmonary vein were compared between groups. Twentyfour hours after the procedure, serum levels of the cardiac biomarkers, including troponin-T, creatine kinase, and creatine kinase-MB, were higher in the HBA group than in the CBA group. Atrial fibrillation recurrence did not differ between the groups within 6 (3% versus 11%; P =0.36) or 12 months (16% versus 16%; P =1.00). Conclusions: Although HBA lesions appear to be smaller than CBA lesions, middle-term outcomes are not statistically different between these balloon modalities.